Love thy neighbor: A guide for implementing safe school initiatives for LGBTQ students in nonaffirming religious communities - Ginicola, Misty M; Smith, Cheri; Rhoades, Elizabeth (Journal of LGBT Issues in Counseling, 2016)
Although setting up a safe school is an important task for a school counselor, his or her efforts may be resisted when attempting to develop a safe school initiative in a religious community; for example, one conservative-based website gives parents explicit instructions on how to fight a school's safe schools initiatives. This article provides a review of the issues involved and a specific framework for school counselors who wish to set up a Safe Schools Initiative in the context of a resistant atmosphere, using a social justice framework. © 2016 Taylor & Francis Group, LLC.
Keywords: LGBTQ; dept.csp; religious conflict; safe schools; school counseling; social justice